The year in cardiology: aorta and peripheral circulation - Heiss, Christian; Pitcher, Alex; Belch, Jill; De Carlo, Marco; Reinecke, Holger; Baumgartner, Iris; Mazzolai, Lucia; Aboyans, Victor (SA Heart Journal, 2020)
Like previous years, the current article reviews groundbreaking science published in 2019 in the area of aortic and peripheral arterial diseases (PAD), as well as venous thromboembolic disease (VTE), which will affect our daily clinical practice.